Answer:
x=-2, y=-2. (-2, -2).
Step-by-step explanation:
2x-5y=6
-2x+10y=-16
-------------------
5y=-10
y=-10/5=-2
2x-5(-2)=6
2x+10=6
2x=6-10
2x=-4
x=-4/2=-2
Answer:
A 5
Step-by-step explanation:
Parts on the left have the same ratio as parts on the right.
... x/(x+5) = (x -2)/(x +1)
Multiplying by (x+5)(x+1), we get
... x(x +1) = (x -2)(x +5)
... x² +x = x² +3x -10 . . . . eliminate parentheses
... 0 = 2x -10 . . . . . . . . . . subtract x²+x
... 0 = x -5 . . . . . . . . . . . . divide by 2
... 5 = x . . . . . . . . . . . . . . . add 5
Answer:
12/4=3 or 12/3=4
Step-by-step explanation:
because multiplication is the opposite of division